Proceedings of the 11th ACM Conference on Computer and Communications Security 2004
DOI: 10.1145/1030083.1030116
|View full text |Cite
|
Sign up to set email alerts
|

A PIN-entry method resilient against shoulder surfing

Abstract: Magnetic stripe cards are in common use for electronic payments and cash withdrawal. Reported incidents document that criminals easily pickpocket cards or skim them by swiping them through additional card readers. Personal identification numbers (PINs) are obtained by shoulder surfing, through the use of mirrors or concealed miniature cameras. Both elements, the PIN and the card, are generally sufficient to give the criminal full access to the victim's account. In this paper, we present alternative PIN entry m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
138
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(149 citation statements)
references
References 22 publications
1
138
0
3
Order By: Relevance
“…Roth et al [26] focused their attention on handling PINs of magnetic strip cards, where each PIN digit is inserted by the user in several rounds. In each round, the system shows the possible digits randomly partitioned into two sets, whose elements are depicted with a different color (e.g.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Roth et al [26] focused their attention on handling PINs of magnetic strip cards, where each PIN digit is inserted by the user in several rounds. In each round, the system shows the possible digits randomly partitioned into two sets, whose elements are depicted with a different color (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…The intersection of sets selected at every round gives the PIN digit for the user. The security of the scheme against attacks performed by adversaries either with human memorization capabilities or with camera recording capabilities was also discussed in [26].…”
Section: Related Workmentioning
confidence: 99%
“…Static password schemes, 13 one-time password (OTP) schemes [18], password schemes resilient to shoulder surfing attacks [12,27], and schemes generating domain-specific passwords from a combination of single user-chosen passwords and multiple domain-specific keys [26,11] can all be used to authenticate users and thereby solve parts of the problem of phishing and/or IDF. Our scheme can be viewed as a careful combination of known and modified tools and techniques (e.g.…”
Section: Related Work and Comparisonmentioning
confidence: 99%
“…McCune [27] proposes the use of a visual channel to secure authentication, users scan barcodes with their smartphones. Roth et al [28] propose a challenge-based approach to PIN-entry that minimises the threat of user's being observed entering their authentication secret . Nevertheless, while the proposed approach is not particularly burdensome, especially so when contrasted with the aforementioned approaches, Roth et al reported that users simply did not perceive the benefits as worth the cost of entry.…”
Section: Introductionmentioning
confidence: 99%